EKSISTENSI SATUAN POLISI PAMONG PRAJA (SATPOL PP) DALAM PENEGAKAN ATURAN ALKOHOL DI KABUPATEN LUWU TIMUR - Haedar Djidar; Dandi Darmadi; Yudi Burhan (Halu Oleo University, 2024)
One of the roles of the Civil Service Police Unit in East Luwu Regency is the Enforcement of Regional Regulation Number 3 of 2017 Concerning Control, Supervision and Order of the Production, Distribution and Sale of Alcoholic Beverages in East Luwu Regency. The purpose of this paper is to determine the Existence Of The Civil Servant Police Unit (Satpol PP) In the Enforcement Of Alcohol Regulations In East Luwu Regency. The research method uses a qualitative approach, a combination of a normative legal approach, and the addition of various empirical elements. The results of the study show that the existence of the Civil Service Police Unit in enforcing Regional Regulation Number 3 of 2017 concerning Control, Supervision and Order of the Production, Distribution and Sale of Alcoholic Beverages in East Luwu Regency is one form of contribution by the Civil Service Police Unit in the form of (1) intensive and external supervision, (2) guidance for places selling alcoholic beverages illegally, and (3) order for places selling alcoholic beverages illegally, the effectiveness of efforts to supervise the distribution of alcoholic beverages in East Luwu Regency.